1990
DOI: 10.1093/geronj/45.2.m45
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immunity as a Predictor of Morbidity and Mortality in Subjects Over 60

Abstract: Previous studies have suggested an association between depressed cell-mediated immunity and increased mortality in elderly persons. However, the effects of age and existing disease on this association have not been adequately addressed. We studied the association between cell-mediated immunity and subsequent morbidity and mortality in 273 initially healthy persons 60 years of age and older. In 1979, two tests of cell-mediated immunity were conducted--mitogen stimulation with phytohaemagglutinin, and delayed hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(132 citation statements)
references
References 0 publications
2
125
0
5
Order By: Relevance
“…The senescent decrease in antioxidant levels supports the free radical theory of ageing, and provides a rationale for decreasing the rate of ageing by supplementing the diet with these antioxidants (Miquel & Weber, 1990). Previous studies from our laboratory, in old mice as well as in elderly men and women, have demonstrated the beneficial effects in vitro and in vivo, on the immune functions, of the antioxidants mentioned above (De la Fuente et al, 1998a,b;De la Fuente & Victor, 2000;Ferrández et al, 1999), and we should emphasize that an adequate immune system is a marker of health and longevity (Wayne et al, 1990). Moreover, the antioxidant doses should be higher in old animals than in the adult in order to improve the immune system (De la .…”
Section: Free Radicals and Antioxidants In The Immune Systemmentioning
confidence: 65%
See 1 more Smart Citation
“…The senescent decrease in antioxidant levels supports the free radical theory of ageing, and provides a rationale for decreasing the rate of ageing by supplementing the diet with these antioxidants (Miquel & Weber, 1990). Previous studies from our laboratory, in old mice as well as in elderly men and women, have demonstrated the beneficial effects in vitro and in vivo, on the immune functions, of the antioxidants mentioned above (De la Fuente et al, 1998a,b;De la Fuente & Victor, 2000;Ferrández et al, 1999), and we should emphasize that an adequate immune system is a marker of health and longevity (Wayne et al, 1990). Moreover, the antioxidant doses should be higher in old animals than in the adult in order to improve the immune system (De la .…”
Section: Free Radicals and Antioxidants In The Immune Systemmentioning
confidence: 65%
“…Thus, the immune system has been proposed as a marker of biological age and life span since a suboptimal immune function may significantly contribute to morbidity and mortality in the elderly. Moreover, an association between immune function and individual longevity has been suggested (Wayne et al, 1990).…”
Section: Ageing and The Immune Systemmentioning
confidence: 99%
“…The illness patterns in the elderly reflect both a deterioration of immune function and increased incidence of upper respiratory infections, shingles, tuberculosis and cancer. Moreover, prospective studies indicate that older persons with low delayed-type hypersensitivity skin test (DTH) responses have higher morbidity, are less selfsufficient, and have a higher incidence of post-operative complications and mortality compared with those with normal DTH responses (90)(91)(92).…”
Section: Immune Functionmentioning
confidence: 99%
“…In the cells of innate immunity, the phagocytic cells show functions that decrease with ageing and others that are over activated (2,(11)(12)(13) , whereas the anti-tumoral activity of natural killer (NK) cells, in most of the work, shows an age-related decrease (2,11,14) . In addition, it has been demonstrated that the competence of the immune system is an excellent marker of health (2,4,8,15,16) and several age-related changes in immune functions, such as low T-cell proliferative responses, IL-2 secretion and NK cell cytotoxicity, have been linked to longevity (2,15,16) . In previous studies, the earlier-mentioned functions and other immune functions, in lymphocytes and phagocytes, have been established as markers of biological age and therefore as predictors of longevity (2,13,16,17) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%